Intersubjectivity and the Emergence of Words - Terrace, Herbert S.; Bigelow, Ann E.; Beebe, Beatrice (Frontiers in Psychology, 2022)
Infants engage in two nonverbal intersubjective relations during their first year that are precursors of language. Trevarthen, a pioneer in the study of intersubjectivity, referred to them as primary and secondary intersubjectivity. The former, a dyadic coordination between an infant and a caregiver, begins at birth. The latter, a triadic coordination which develops around 9 months, allows an infant and a caregiver to share attention to particular features of the environment. Secondary intersubjectivity is a precursor of an infant’s ability to begin to produce words, at around 12 months. Much research on the origins of language has focused on secondary intersubjectivity. That is unfortunate because it neglects the fact that secondary intersubjectivity and the origins of language are built on the foundation of primary intersubjectivity. It also ignores the evolutionary origins of intersubjectivity and its uniquely human status (why only humans learn language). This article seeks to address these problems by relating the literature on primary intersubjectivity, particularly research on bi-directional and contingent communication between infants and mothers, to joint attention and ultimately to words and language. In that context, we also discuss Hrdy’s hypothesis about the influence of alloparents on the evolution of intersubjectivity.